A Tunable, Stable, and Bioactive MOF Catalyst for Generating a Localized Therapeutic from Endogenous Sources. (12th September 2014) - Harding, Jacqueline L.; Metz, Jarid M.; Reynolds, Melissa M.
<x xml:space="preserve">Abstract</x> The versatile chemical and physical properties of metal organic frameworks (MOFs) have made them unique platforms for the design of biomimetic catalysts, but with only limited success to date due to instability of the MOFs employed in physiological environments. Herein, the use of Cu(II)1, 3, 5‐Benzene‐tris‐triazole (CuBTTri) is demonstrated for the catalytic generation of the bioactive agent nitric oxide (NO) from endogenous sources, S‐nitrosothiols (RSNOs). CuBTTri exhibits structural integrity in aqueous environments, including phosphate buffered saline (76 h, pH 7.4, 37 °C), cell media used for in vitro testing (76 h, pH 7.4, 37 °C), and fresh citrated whole blood (30 min, pH 7.4, 37 °C). The application of CuBTTri for use in polymeric medical devices is explored through the formation of a composite CuBTTri‐poly by blending CuBTTri into biomedical grade polyurethane matrices. Once prepared, the CuBTTri‐poly material retains the catalytic function towards the generation of NO with tunable release kinetics proportional to the total content of CuBTTri embedded into the polymeric material with a surface flux corresponding to the therapeutic range of 1–100 nm cm−2 min−1, which is maintained even following exposure to blood.